Thermal Decomposition of Compounds Derived from 2H-Dihydropyran: A Computational Study - Pablo Ruiz; Sara Bucheli; Paula Fernández; Silvia Quijano; Jairo Quijano; Jair Gaviria (Chemistry)
This research study computationally examined the thermal decomposition of three molecules, 3,6-dihydro-2H-pyran, 4-methyl-3,6-dihydro-2H-pyran, and 2,6-dimethyl-3,6-dihydro-2H-pyran, using the PBE0/6-311+G(d,p) level of theory and a concerted mechanism with a 6-member cyclic transition state. For this analysis, kinetic and thermodynamic parameters were calculated for reactions within a temperature range of 584 to 633 K and compared with experimental data. Our results revealed that methyl substituents at 2, 4, and 6 positions decrease the activation free energy of the molecules. Even though the evaluated reactions exhibited high absolute synchronicity, significant differences were observed regarding the extent of their bond evolution.